Beira Railway Station: Modern Architecture as an urban catalyst - Oliveira, Maria Manuel (2020)
Artigo aceite para publicação em: 16th International Docomomo Conference, Tokyo 2020 - Inheritable Resilience: Sharing Values of Global Modernities, 6th to the 15th September 2020